Kedudukan Perempuan Sasak dalam Tradisi Merariq: Studi Kasus Keadilan dan Kesetaraan Gender - Ani Wafiroh; Alfathoni, Ahmad Fiqqih; Muktamar Ibrahim (Lembaga Teewan Journal Solutions, 2026)
This study examines the position of Sasak women in the merariq tradition on Lombok Island with an emphasis on the perspective of gender justice and equality. The merariq tradition as a typical marriage practice of the Sasak people is often understood as a symbol of male courage and social legitimacy in forming a family, but on the other hand, it leaves problems related to women's position and rights. This study aims to analyse how the construction of women's position in the practice of merariq and the extent to which the tradition reflects the principles of justice and gender equality. The method used is qualitative research with a sociological approach to Islamic law and gender, through case studies and descriptive-analytical analysis. The results show that the practice of merariq contains ambivalence: on the one hand, it shows gender inequality through the lack of women's consent, social pressure, and marginalisation in decision-making; But on the other hand, it also opens up a space for negotiation for women in determining their life partner. Thus, justice in the Merariq tradition cannot be seen formally but must be analysed substantively through women's experiences and the power relations that surround them.